Short communication: Systematic review on effectiveness of micro-induction approaches to buprenorphine initiation. (March 2021) - Moe, Jessica; O'Sullivan, Fiona; Hohl, Corinne M.; Doyle-Waters, Mary M.; Ronsley, Claire; Cho, Raymond; Liu, Qixin; Azar, Pouya
Highlights: Buprenorphine micro-induction seeks to improve patient comfort and avoid withdrawal. Existing case studies/series describe variable regimens that lack standardization. Poor quality evidence limits conclusions regarding optimal dosing and indications. Rigorous studies evaluating effectiveness and safety of micro-induction are needed. Abstract: Background/objectives: Micro-induction is a novel buprenorphine induction approach that seeks to avoid withdrawal and minimize precipitated withdrawal, both barriers to standard inductions. We aimed to synthesize evidence on micro-induction effectiveness, and regimens described. Methods: We searched scientific databases and grey literature for studies including adolescents or adults with opioid use disorder who received buprenorphine micro-induction. Study selection, data extraction and quality assessments occurred in duplicate. We narratively synthesized results. Results: We screened 4, 752 citations and included 19 case studies/series and one feasibility study (n = 57 patients; mean age 38 years [SD 12.0]; 57.9% male [33/57]). Studies described 26 regimens; starting and maintenance doses ranged from 0.03 to 1.0 mg, and 8 to 32 mg, respectively. We calculated rate of increase to 8 mg. All patients achieved the desired maintenance dose. Among 54 patients in whom precipitated withdrawal was not reported, mean increases were 1.36 mg/day (SD 0.41). For three patients in whom precipitated withdrawal was specifically reported, mean increase was 1.17 mg/day (SD 0.11). All studies were low quality. Discussion: Described regimens are highly variable. Inconsistent reporting, selection bias, and poor quality evidence limit conclusions regarding optimal dosing, and patient characteristics and clinical settings in which micro-induction is likely beneficial. Conclusions: This systematic review provides the most up-to-date synthesis on buprenorphine micro-induction regimens. Rigorous studies evaluating effectiveness and safety of micro-induction, and patient and clinical factors influencing its success, are needed.